Uso de la creatinina como indicador de la excreción urinaria en bovinos Nellore (2012)
ABSTRACT: Urinary excretion is fundamental for the understanding of several variables related to ruminant nutrition. The total collection of urine from grazing animals is a complex and difficult procedure, while in confined animal it requires the installation of funnels or urinary catheters that generate discomfort along with an increased risk of injury. Objective: the aim of this study was to validate the predictive ability of urine creatinine on urine output, in comparison with the total collection method. Methods: five Nelore animals were used. Animals were kept in confinement conditions and were offered feed and water ad libitum. The total volume of urine produced, determined by total collection in metabolic cages was compared with the estimated production calculated from creatinine excretion. Spot samples collected four hours after feeding the animals were analyzed for creatinine concentration during four experimental periods. Results: the statistical significance of paired t-test and the trend of the regression slope in the Bland-Altman analysis allow concluding that creatinine excretion, under our experimental conditions, was not an adequate predictor of urine volume. Conclusions: creatinine concentration in spot samples can be considered as the critical factor in this methodology due to the common diurnal variations of urine output and, therefore, the variations in the excretion of the metabolite.